Live Birth After the Transfer of Embryos Obtained by Fertilization of Vitrified Oocytes. Report of One Case [Parto Tras la Transferencia de Embriones Generados por Fecundación de Ovocitos Vitrificados. Comunicación de Un Caso] - Schwarze-Meza, J (2011)
Sin Editorial Disponible